MUNDU: Garciniaxanthochymus Hook.f. ATAU G. dulcis (Roxb.) Kurz. - Nanda Utami; Rismita Sari (BERITA BIOLOGI, 2009)
"Mundu" is common name for one of the member of Clusiaceae family (manggis-manggisan).In scientific writing it is sometimes called Garcinia xanthochymus Hook.f. or G. dulcis (Roxb.)Kurz. To determine the correct name for these two kinds of plant a study was conducted to review its taxonomic status. Based on morphological data, anatomical and phylogenetic analysis it is showed that the two species is separated but there are closely related, and in according to International Code of Botanical Nomenclature Garcinia xanthochymus Hook.f is the correct name for "MUNDU"